Groundwater Recharge Assessment in the Gunungsewu Karst Area Using the APLIS Method and a Modified Soil Physics Approach - Mujiyo, Mujiyo; Surachman, Rinta Faradila; Sumani, Sumani; Ariyanto, Dwi Priyo (Green Engineering Society, 2025)
Karst areas experience annual drought, making it essential to preserve potential groundwater recharge areas. This study aims to assess the level of groundwater recharge and its spatial distribution in karst regions, with a case study in the Gunungsewu karst area, Paranggupito sub-district, Wonogiri Regency. This research employed the APLIS method (Altitude, Slope, Lithology, Infiltration and Soil) and collected data by creating a Land Mapping Unit (LMU) map. The LMU was generated through an overlay of land use, soil type, slope, rock type, and rainfall, resulting in 20 LMUs. The observed parameters included elevation, slope, soil type, lithology, soil infiltration, and texture, with modification incorporating porosity as an actual soil parameter. Observations and sampling were conducted, and data analysis involved ANOVA and correlation tests to assess the influence of topography on groundwater recharge distribution and its correlation with soil characteristics. The research results indicate that groundwater recharge is classified into medium and high categories. The distribution of groundwater recharge is influenced by topography and soil infiltration, with the highest recharge occurring on slopes of 0-3% and high infiltration values.